Development of an Evaluation Instrument for Attitude and Skills in Islamic Religious Education for Senior High School Students (Phase E). - Irwansyah; Santi Lisnawati; Wido Supraha (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
Evaluation in Islamic Religious Education (PAI) at the senior high school level should assess not only cognitive achievement but also students’ attitudes and skills as part of authentic assessment in the Merdeka Curriculum. However, teachers often face difficulties in conducting objective affective and psychomotor assessments due to the lack of structured and validated instruments. This study aims to develop and examine the feasibility of an evaluation instrument for assessing attitudes and skills in Islamic Religious Education for Phase E senior high school students. This study employed a Research and Development approach using the ADDIE model. Data were collected through curriculum analysis, expert validation, and limited field testing. The development process included designing assessment indicators, constructing instrument items and rubrics, revising based on expert feedback, and conducting limited trials. The results show that the developed attitude and skills evaluation instruments are feasible for use. Expert validation results indicated a very good level of validity, while limited field trials showed that the attitude instrument was categorized as very good and the skills instrument as good. Therefore, the developed instruments can be used as structured and authentic tools to evaluate affective and psychomotor learning outcomes in Islamic Religious Education at the senior high school level.